The Role of Islamic Religious Education Teachers in Guiding Students' Islamic Communication Ethics in the Digital Era - Putri Alifah Trsina Murti; Nurjanah (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2025)
The development of technology has a very significant influence on the way students communicate which really requires the active role of teachers in directing interactions in accordance with Islamic values. PAI teachers have an important role in managing Islamic communication ethics in the digital world. This study aims to look at the role of PAI teachers in managing students' Islamic communication in the digital era as well as the strategies used by PAI teachers in shaping Islamic communication ethics. This research uses a qualitative approach with data collection techniques through interviews, observations, and documentation carried out at SMA Muhammadiyah 18 Jakarta. The results of the study show that PAI teachers function as good role models, spiritual guides, and facilitators in Islamic digital literacy learning. Teachers also apply learning strategies in the form of projects and religious reflections that are integrated with digital media to instill the values of politeness, responsibility, and civilized ways of communicating on social media. The main factor that supports the success of this program is the cooperation between teachers, principals, and parents in building a digital environment based on religion and education and showing that students are positive about the teacher's efforts, which can be seen from the increased awareness of ethics and polite communication in the digital world. This research concludes that PAI learning combined with digital literacy has an important role in building Islamic communication ethics.